2009
DOI: 10.1097/aog.0b013e3181b5c9e8
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and Analytic Techniques Used in Clinical Research

Abstract: Objective To describe research methodology and statistical reporting of published articles in high impact factor, general medical journals compared to moderate impact factor obstetric and gynecology journals. Methods A cross-sectional analysis was performed on 371 articles published from January to June 2006, in 6 journals (high impact factor group—Journal of the American Medical Association, Lancet, the New England Journal of Medicine; moderate impact factor group—American Journal of Obstetrics and Gynecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…4 The present study found a significant association between RCT quality and a high impact factor, as did Bausch et al 8 Kuroki et al found that the proportion of highquality RCTs in high-impact-factor journals was nearly 3 times that in journals with moderate impact factor. 18 In the present study we found that the proportion of highquality RCTs in the high-impact-factor journals was nearly 1.5 times that in the journals with impact factor Ͻ 5. There are several potential explanations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…4 The present study found a significant association between RCT quality and a high impact factor, as did Bausch et al 8 Kuroki et al found that the proportion of highquality RCTs in high-impact-factor journals was nearly 3 times that in journals with moderate impact factor. 18 In the present study we found that the proportion of highquality RCTs in the high-impact-factor journals was nearly 1.5 times that in the journals with impact factor Ͻ 5. There are several potential explanations.…”
Section: Discussionmentioning
confidence: 50%
“…Second, the editing criteria of the editors, reviewers, and statistical consultants may be stricter. 18 The trials in the general medical journals, which have higher impact factors, had better methods than those in the respiratory journals. The overall trial registration rate was 64%, and trial registration affected the adequacy of allocation, allocation concealment, and double-blinding.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier reports, Hayashino and colleagues demonstrated that RCTs accounted for 2.1% of all research articles from Japan published in the top 10 cardiovascular journals overseas 9. Kuroki and colleagues reported that the proportion of RCTs among published articles in the gynaecology field was 35% in high impact factor journals, such as the New England Journal of Medicine , the Lancet , and the Journal of the American Medical Association , and 12% in journals with a moderate impact factor, similar to that of Japanese cardiovascular journals 10. This study only assessed the recent 10-year trends in the proportion of RCTs published in Japanese cardiovascular journals, and further continuous observation is needed to evaluate whether the proportion of RCTs in the cardiovascular field will increase or not.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, the present research study focused on a selected group of leading general journals. In 2006 the proportion of RCTs published among JAMA, Lancet and NEJM was almost 3 times greater than obstetric and gynecology journals (Kuroki, Allsworth & Peipert, 2009). In addition, trials published in general medical journals had higher quality scores than those in specialist journals .…”
Section: Discussionmentioning
confidence: 99%